# (x3 + x² - 12x-13) = (x-2)

how to remainder using remainder theorem

Answers: 1

## Answers

(x3 + x² - 12x-13) = (x-2)how to remainder using remainder theorem...

r= -25

answer:

x²-x-2, remainder: 8

answer:

P(3) = - 58

Step-by-step explanation:

P(x) = (3)⁴ + 3(3)³ - 16(3)² 2(3) - 7

P(x) = 12 + 27 - 96 - 1

P(x) = 39- 97

P(x) = - 58

answer:

1. x-2 ÷ -6x² + 2x + 8 = -6 + 14 + 36/x-2

answer:

123456789101121214151617181920

answer:

Step-by-step explanation:

The -3 to positive 3in the column is 1, 2,-15, and -36in the outside of the column is positive 3bring down 1 the outside 3 multiply to the bringdown 1 and when you get the multiply of 3 to 1 and then add to the next column is 2 and continous to the until the endthis is the given right Its will become when the 0 answer is not to going write the 0 on the equationANSWER:

MAG TANONG KA KAY ALBERT EINSTEIN

EXPLENATION:

MATALINO SYA

I hope this answer helps you. Medyo mahaba kase at matatagalan ako sa pagsolve. Just remember to substitute "x" or "a"

Number 1 is given for you as your basis.

If there are any questions, pakicomment na lang po :>

The remainder would be x+3

Step-by-step explanation:

Remainder Theorem states that when a polynomial f(x) is divided by (x-a), the remainder is f(a).

Hence:

x - a = 0

x = a

Given:

Polynomial dividend: 2x³ - x² - 2x - 1Divisor (factor): x + 1Identify a from the divisor:

x + 1 = 0

x = - 1

x = a

a = -1Find the remainder, x =a = -1:

f(a) = 2x³ - x² - 2x - 1

f(-1) = 2(-1)³ - (-1)² - 2(-1) - 1

f(-1) = 2(-1) - (1) + 2 - 1

f(-1) = -2 - 1 + 2 - 1

f(-1) = -2 The remainder is -2.#CarryOnLearning